Identifying a Novel Pathogenic Mutation in Exon 3 of ARID1A Gene in Colon Cancer - Mehran Erfani; Pooneh Mokarram; Maral Mokhtari; Jafar Fallahi (Middle East journal of cancer, 2020)
ARID1A, a bona fide tumor suppressor, is the third most mutated gene in human colorectal cancer. In this paper, we reported the identification of a novel mutation in one of 20 primary human colorectal cancer tumors. Sanger sequencing of the exon 3 of the ARID1A gene revealed a novel heterozygous non-sense mutation of the c.1653C>G. This resulted in the premature termination of the 2285 amino acid protein at the 551st codon. Mutation Taster predicted this novel mutation to be pathogenic. Immunohistochemical analysis revealed the loss of ARID1A protein expression in cancerous tissues harboring ARID1A mutation. As far as we know, this is the first report on the mutation of ARID1A gene in an Iranian patient. This mutation can expand the spectrum of ARID1A gene pathogenic mutations among colorectal cancer patients.